Utility of blood tests in screening for metabolic disorders in kidney stone disease. (4th October 2020) - Eyre, Katie S.; Lewis, Francesca; Cui, Helen; Grout, Emily; Mihai, Radu; Turney, Benjamin W.; Howles, Sarah A.
Abstract : Objectives: To determine the clinical utility of blood tests as a screening tool for metabolic abnormalities in patients with kidney stone disease. Subjects and Methods: Clinical and biochemical data from 709 patients attending the Oxford University Hospitals NHS Foundation Trust for assessment and treatment of kidney stones were prospectively collected between April 2011 and February 2017. Data were analysed to determine the utility of serum calcium, parathyroid hormone (PTH), urate, chloride, bicarbonate, potassium and phosphate assays in screening for primary hyperparathyroidism, normocalcaemic hyperparathyroidism, hyperuricosuria, distal renal tubular acidosis (dRTA) and hypercalciuria. Results: An elevated serum calcium level was detected in 2.3% of patients. Further investigations prompted by this finding resulted in a diagnosis of primary hyperparathyroidism in 0.2% of men and 4.6% of women for whom serum calcium was recorded. An elevated serum PTH level in the absence of hypercalcaemia was detected in 15.1% of patients. Of these patients, 74.6% were vitamin D‐insufficient; no patients were diagnosed with normocalcaemic hyperparathyroidism. Hyperuricosuria was present in 21.6% of patients and hypercalciuria in 47.1%. Hyperuricaemia was not associated with hyperuricosuria, nor was hypophosphataemia associated with hypercalciuria. No patient was highlighted as being at risk of dRTA using serum chloride and bicarbonate as screening tests. Conclusion: This study indicates that individuals presenting with renal calculi should undergo metabolic screening with a serum calcium measurement alone. Use of additional blood tests to screen for metabolic disorders is not cost‐effective and may provide false reassurance that metabolic abnormalities are not present. A full metabolic assessment with 24‐h urine collection should be undertaken in recurrent stone formers and in those at high risk of future stone disease to identify potentially treatable metabolic abnormalities.